Fimepinostat (CUDC‐907) in patients with relapsed/refractory diffuse large B cell and high‐grade B‐cell lymphoma: report of a phase 2 trial and exploratory biomarker analyses - Landsburg, Daniel J.; Barta, Stefan K.; Ramchandren, Radhakrishnan; Batlevi, Connie; Iyer, Swaminathan; Kelly, Kevin; Micallef, Ivana N.; Smith, Sonali M.; Stevens, Don A.; Alvarez, Mariano; Califano, Andrea; Shen, Yao; et al. (British journal of haematology, 2021)
Summary Fimepinostat (CUDC‐907), a first‐in‐class oral small‐molecule inhibitor of histone deacetylase and phosphatidylinositol 3‐kinase, demonstrated efficacy in a phase 1 study of patients with relapsed/refractory (R/R) diffuse large and high‐grade B‐cell lymphomas (DLBCL/HGBL), particularly those with increased MYC protein expression and/or MYC gene rearrangement/copy number gain (MYC‐altered disease). Therefore, a phase 2 study of fimepinostat was conducted in this patient population with 66 eligible patients treated. The primary end‐point of overall response (OR) rate for patients with MYC‐IHC ≥40% (n = 46) was 15%. Subsequently, exploratory pooled analyses were performed including patients treated on both the phase 1 and 2 studies based upon the presence of MYC‐altered disease as well as a biomarker identified by Virtual Inference of Protein activity by Enriched Regulon analysis (VIPER). For these patients with MYC‐altered disease (n = 63), the overall response (OR) rate was 22% with seven responding patients remaining on treatment for approximately two years or longer, and VIPER yielded a three‐protein biomarker classification with positive and negative predictive values of ≥85%. Prolonged durations of response were achieved by patients with MYC‐altered R/R DLBCL/HGBL treated with single‐agent fimepinostat. Combination therapies and/or biomarker‐based patient selection strategies may lead to higher response rates in future clinical trials.